Luxury Vegetative Nitrogen Uptake in Maize Buffers Grain Yield Under Post-silking Water and Nitrogen Stress: A Mechanistic Understanding - Nasielski, Joshua; Earl, Hugh; Deen, Bill (Frontiers in Plant Science, 2019)
During vegetative growth maize can accumulate luxury nitrogen (N) in excess of what is required for biomass accumulation. When post-silking N uptake is restricted, this luxury N may mitigate N stress by acting as an N reserve that buffers grain yield and maintains plant function. The objective of this study was to determine if and how luxury accumulation of N prior to silking can buffer yield against post-silking N and/or water stress in maize. In a greenhouse experiment, maize was grown in high (Nveg) and low (nveg) N conditions during vegetative growth. The nveg treatment did not affect biomass accumulation or leaf area by silking but did accumulate less total N compared to the Nveg treatment. The Nveg treatment generated a reserve of 1.1 g N plant-1. Plants in both treatments were then subjected to water and/or N stress after silking. 15N isotope tracers were delivered during either vegetative or reproductive growth to measure N remobilization and the partitioning of post-silking N uptake with and without a luxury N reserve. Under post-silking N and/or water stress, yield was consistently greater in Nveg compared to nveg due to a reduction in kernel abortion. The Nveg treatment resulted in greater kernel numbers and increased N remobilization to meet grain N demand under post-silking N stress. Luxury N uptake at silking also improved leaf area longevity in Nveg plants compared nveg under post-silking N stress, leading to greater biomass production and increased yield. While post-silking N uptake was similar across Nveg and nveg, Nveg plants partitioned a greater proportion of post-silking N to vegetative organs, which may have assisted with the maintenance of leaf function and root N uptake capacity. These results indicate that N uptake at silking in excess of vegetative growth requirements can minimize the effect of N and/or water stress during grain-fill.